SOLVING SINGLE-OBJECTIVE QUADRATIC ASSIGNMENT PROBLEMS USING SIMULATED ANNEALING ALGORITHM FOR HOSPITAL FACILITY LAYOUT OPTIMIZATION - Moamar Shakir Mahmood; Abdelkarim Ben Habib Elloumi; Enas Abbas Abed (Galaxy International Interdisciplinary Research Journal, 2024)
This research aims to study how to solve quadratic assignment problems using a simulated annealing algorithm for the internal arrangement of hospital facilities. This is done by reviewing the literature related to the algorithm, determining the variables and criteria necessary to evaluate its performance, designing the study and applying the algorithm to hospitals, and the collected data is analyzed. To provide results and recommendations, which contributes to improving squared allocation processes within the hospital and achieving the desired goal of the research.